Trust in COVID-19 policy among public health professionals in Israel during the first wave of the pandemic: a cross-sectional study - Tamar Zohar; Maya Negev; Maia Sirkin; Hagai Levine (BMC, 2022)
Abstract Background The COVID-19 pandemic has highlighted the important role of professionals in designing and communicating effective policies. The purpose of this study was to evaluate the level of trust in the COVID-19 national public health policy among public health professionals in Israel and its correlates during the first wave of the pandemic. Methods A purposive sampling of public health professionals in Israel, through professional and academic public health networks (N = 112). The survey was distributed online during May 2020. Level of trust was measured by the mean of 18 related statements using a 5-point Likert scale, where 1 means not at all and 5 means to a very high extent, and grouped as low and high trust by median (2.75). Results A moderate level of trust in policy was found among professionals (Mean: 2.84, 95% Cl: [2.70, 2.98]). The level of trust among public health physicians was somewhat lower than among researchers and other health professionals (Mean: 2.66 vs. 2.81 and 2.96, respectively, p = 0.286), with a higher proportion expressing low trust (70% vs. 51% and 38%, respectively, p < 0.05). Participants with a low compared to high level of trust in policy were less supportive of the use of Israel Security Agency tools for contact tracing (Mean = 2.21 vs. 3.17, p < 0.01), and reported lower levels of trust in the Ministry of Health (Mean = 2.52 vs. 3.91, p < 0.01). A strong positive correlation was found between the level of trust in policy and the level of trust in the Ministry of Health (rs = 0.782, p < 0.01). Most professionals (77%) rated their involvement in decision making as low or not at all, and they reported a lower level of trust in policy than those with high involvement (Mean = 2.76 vs. 3.12, p < 0.05). Regarding trust in the ability of agencies to deal with the COVID-19 crisis, respondents reported high levels of trust in the Association of Public Health Physicians (80%) and in hospitals (79%), but very low levels of trust in the Minister of Health (5%). Conclusions This study shows that Israeli public health professionals exhibited moderate levels of trust in COVID-19 national public health policy and varied levels of trust in government agencies during the first wave of COVID-19. The level of trust in policy was lower among most of the participants who were not involved in decision making. The level of trust found is worrisome and should be monitored, because it may harm cooperation, professional response, and public trust. Professionals' trust in policy-making during early stages of emergencies is important, and preemptive measures should be considered, such as involving professionals in the decision-making process, maintaining transparency of the process, and basing policy on scientific and epidemiological evidence.